Ideology of Pancasila versus Islamism: Measuring Actions and Reactions of Campus Organs to Permenristekdikti No. 55 of 2018 in UGM and UIN Yogyakarta - Muhsin, Illya (LPPM IAIN Kudus, 2019)
The purpose of this study is to discuss the actions and reactions of the issuance of Permenristekdikti No. 55 of 2018 at Universitas Gadjah Mada (UGM) Yogyakarta and Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, which exhibits an ideological struggle between Pancasila and Islamism. It was found that the fact of the rise of radicalism in the campus realm underlies the issuance of this regulation. Therefore, it becomes a means of fostering the ideology of the nation on campus. In practice, UIN has not yet implemented the regulation, but it has realized the spirit of it in the form of campus rules. There are responses and impacts that occur. However, it is not within the area of student organs, but the institution, and its impact is felt by all students. Meanwhile, at UGM, there is no direct policy yet, but campus organs have been actively discussing and mapping the patterns of movement to be carried out when the regulation is later enacted.